Theoretical and empirical analysis of income inequality and wage differentials: A comparison between the United States and Guatemala - Ashley Owings (Luxembourg Income Study (LIS), 2010)
With the current economic transformation, the widening gap between income and the accumulation of wealth becomes an important area of study. This study reviews wage differentials and a number of economic theories regarding wage determination and labor market incentives. To analyze the wage differential, the study examines empirical data from the United States and Guatemala across income levels via the Luxembourg Income Study data sets. The econometric model proposed examines multiple factors influencing wage rates at the household level including levels of education, household demographics, additional forms of income, transfers, and rates of taxation. Considering the different levels of development between the countries, the empirical data for Guatemala can be compared to the United States and analyzed to ascertain areas of focus to further develop Guatemala's economy by focusing on increasing gains in education and access of public resources across Guatemala.
Keywords: 330; Lohnstruktur; Einkommensverteilung; Privater Haushalt; Bildung; Öffentliche Güter; Guatemala; USA